Upaya Meningkatkan Hasil Belajar Peserta Didik melalui Penerapan Model Pembelajaran Kooperatif Tipe Learning Together - Yuliati, Yuliati (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
This study aims to describe the increase in student learning outcomes through the application of the cooperative learning model with the type of shared learning on absolute value material in class X IPA 1 SMA Negeri 7 Banda Aceh in the 2018/2019 academic year. The location of this research is where the researcher teaches, namely at SMA Negeri 7 Banda Aceh. This research was conducted in the odd semester of the 2018/2019 school year which is planned to be carried out for 3 months from July to September 2018. The subjects of this study were 34 students of class X IPA 1 SMA Negeri 7 Banda Aceh in the 2018/2019 academic year. learners. This research is a classroom action research. The data technique in this study was obtained from the results of cycle tests, observations of teacher and student activities in learning. The data analysis technique used in this research was qualitative descriptive using the proportion formula. The results of the cycle test showed that the average learning outcome in the first cycle was 76.18, while in the second cycle it was 87.29, an increase of 11.11. Completeness of learning in the first cycle was 73.29%, while in the second cycle it was 100%, an increase of 26.47%. The average total teacher activity in carrying out learning in cycle I was 3.5 and in cycle II increased to 4.8, an increase of 1.3. The activity of students in participating in learning in the first cycle was 63.75% and in the second cycle it increased to 90%, an increase of 26.25%. So it can be denied that the application of the cooperative learning model of the type of shared learning can improve student learning outcomes on absolute value material in class X IPA 1 SMA Negeri 7 Banda Aceh in the 2018/2019 academic year.